Building of Anti-Bacterial Smart Sterilization Room Based on Internet of Things Using PIR Sensor and Its Quality Assurances - Ghifar Rachman Nugraha; Sevia Indah Purnama; Muhammad Yusro (Jurnal Teknokes, 2022)
The dangers of bacteria can cause health problems or infections of the respiratory tract. This research is related to the design of an anti-bacterial smart room sterilization system based on the Internet of Things (IoT) using a Passive Infrared Receiver (PIR). This study aims to sterilize with a monitoring and security system with PIR sensors and Blynk platform. Tool testing is carried out by taking 7 data from 1 object with 3 scanario which are sterilization without an object, sterilization by detecting objects, sterilization by detecting objects which is back to the room. In this system each condition is monitored on the Blynk platform. The advantage of this system is managed and monitored safety sterilization process remotely by Blynk. This tool has also gone through measurement quality assurance testing by adopting ISO 17025 including sensitivity, selectivity, precision, working range , tool toughness, and measurement uncertainty. The quality of service (QoS) test in this system gets an average delay of 122 milliseconds, throughput of 1045 bit/s and packet loss of 0.06%. This sterilizer can be monitored and operated remotely and is equipped with a security system.